Effectiveness Of Modeling Techniques Through Symbolic Models To Improve Career Planning Of Students Of The Al-Ikhlas Putri Organizational Boarding School Singosari (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
The Effectiveness of Modeling Techniques Using Symbolic Models to Improve Career Planning for Female Students at the Al-Ikhlas Orphan and Underprivileged Islamic Boarding School in Singosari. This study aims to evaluate the effectiveness of group guidance services using the symbolic modeling technique to improve the career planning of female students at the Al-Ikhlas Yatim Dhu'afa Islamic Boarding School in Singosari. The study addresses issues faced by students who experience confusion in determining their career plans after leaving the boarding school. This research employs a pre-experimental method using a Quasi-Experimental Design with the Equivalent Time Series Design method, involving a sample of 11 students. Data collection methods include observation, interviews, and questionnaires. Before being distributed, the questionnaires were tested for validity and reliability. The data analysis technique used is the Wilcoxon Match Pairs Test. The results of this study show that the symbolic modeling technique can be a practical and effective solution to help Islamic boarding school students improve their career planning skills. This is evidenced by a significant increase in students' scores at each post-test stage compared to the pre-test results. The average student score increased from 41.73 (low category) in the pre-test to 113.27 (high category) in the fourth post-test. This average increase of 171% demonstrates the success of the intervention in building career planning skills, particularly for students initially in the low category. This approach can be applied more broadly to other aspects of personal development, such as emotional management, interpersonal communication, and decision-making.